Local Institution Model of Tambrauw Conservation in West Papua - Sepus M. Fatem; San Afri Awang; Ahmad Maryudi; Satyawan Pudyatmoko; Jonni Marwa (Jurnal Ilmu Kehutanan)
Political Commitment to establishing Tambrauw as a conservation district in West Papua, has led to changes in conventional governance towards conservation management. Thus the institution as a unit responsible for organizing conservation district activities needs to be designed to oversee the policies of the conservation district concerned. This study aims to design a local institutional model of Tambrauw Regency as a Conservation District. The design process of the local institutional model was carried out from June 2013 to December 2017 following the research and development method. Research data obtained from: (1) the results of expert interviews; (2) field notes, and (3) data suggesting improvements to the initial model draft and observers' observations on the implementation of trials (FGDs / Consultations) on a small and large scale. To see the significance of the comparison of the existing institutional models in the form of regional apparatus organizations (OPD) and the conservation district institutions offered, a t-test was conducted. The design process of the conservation district's local institutional building was carried out about the 8 key design principles offered by Ostrom on effective management institutions for common property. The results showed that conservation district institutions should be developed as a unit responsible for the mechanism of conservation district performance, which is non-body and more emphasized on the coordination function by the Agency for Regional Development Tambrauw Regency as coordinator of regional development planning.